(untitled) (Research, Society and Development, 2022)
The research will address the use of botulinum toxin in the prevention of dynamic wrinkles, with the objective of carrying out a bibliographic research on the use of botulinum toxin for aesthetic purposes. The aging process occurs from the age of 30, whose changes can be classified in two ways: intrinsic and extrinsic aging. Wrinkles are called marked furrows and can be fine and expression lines, which have loss of elasticity causing sagging, thus, presenting the appearance of being drier and thinner. The research becomes relevant because it is a substance that has been widely used in the area, and, therefore, it is necessary to study its use in combating the prevention of dynamic wrinkles, so that its application has numerous possibilities, so that they are still in full evolution, in order to guarantee successful results, avoiding adverse reactions.